National data on the early clinical use of non‐invasive prenatal testing in public and private healthcare in Denmark 2013–2017. (24th February 2021) - Lund, Ida C. B.; Petersen, Olav B.; Becher, Naja H.; Lildballe, Dorte L.; Jørgensen, Finn S.; Ambye, Louise; Skibsted, Lillian; Ernst, Anja; Jensen, Ann N.; Fagerberg, Christina; Brasch‐Andersen, Charlotte; Tabor, Ann; et al.
Abstract: Introduction: In Denmark, non‐invasive prenatal testing (NIPT) has been used since 2013. We aimed to evaluate the early clinical use of NIPT in Danish public and private healthcare settings before NIPT became an integrated part of the national guidelines on prenatal screening and diagnosis in 2017. Material and methods: NIPT data were collected between March 2013 and June 2017 from national public registries and private providers. Results from follow‐up samples (chorionic villi, amniotic fluid, postnatal blood or fetal tissue) were included from The Danish Cytogenetics Central Registry and indications and outcome from The Danish Fetal Medicine Database. Results: A total of 3936 NIPT results were included in the study from public hospitals (n = 3463, 88.0%) and private clinics (n = 473, 12.0%). The total number of prenatal tests was 19 713 during the study period: 20% were NIPT analyses (n = 3936) and 80% invasive procedures (n = 15 777). Twenty‐five percent of NIPTs in the private clinics were performed before gestational week 11 +0, whereas NIPT in public settings was used only after combined first trimester screening ( P  < .001). Regardless of indication, the national public sensitivity was 96.9% (95% CI 82.0%‐99.8%) for trisomy 21, 100% (95% CI 46.3%‐100%) for trisomy 18, 100% (95% CI 5.5%‐100%) for trisomy 13, and 87.0% (95% CI 74.5%‐92.4%) for any fetal chromosomal aberration. Forty‐seven true‐positive NIPT results included cases of common aneuplodies (trisomy 21, n = 31; trisomy 18, n = 5; and trisomy 13, n = 1), sex chromosomal aberrations (n = 7) and atypical chromosomal aberrations (n = 3). One false‐negative NIPT result occurred (trisomy 21). Of 47 cases, 21 (45%) cases with a true‐positive NIPT result resulted in live births by choice; 11 of these children had Down and 4 had Edwards syndrome. Conclusions: The total number of NIPT analyses was low compared with the number of invasive procedures in the implementation period. In contrast to the generally high termination rate after a positive result following invasive testing in Denmark, a high proportion of true‐positive NIPT results from the public setting resulted in live births. NIPT may be an important risk‐free alternative to invasive testing for a minority of women in the public setting who wish to use prenatal genetic testing for information only and not for reproductive decision‐making.